Investigation of Nanostructures on the Crepuscular 'Eyespot' of the Caligo Memnon Nymphalidae Felder (1866) Butterfly. (2015) - Sackey, J.; Nuru, Z.Y.; Berthier, S.; Maaza, M.
Abstract: This paper investigates the self-assembled chitin based nanostructures of the Caligo Memnon Nymphalidae Felder (1866) butterfly's scales that are responsible for the colour formation on the butterfly's "artificial eyespot". The Fourier transform analysis of the digital scanning electron microscope images and the calculation of the corresponding half-width Airy disc allowed an effective estimation of the temporal resolution of this "artificial eyespot" as well as its optical sensitivity and optical absorption/light trapping. It was observed that Land equation remains an excellent tool for computing optical sensitivity of nanostructure materials.